The Emerald handbook of management and organization inquiry - Boje, David M.; Sanchez, Mabel (Bingley, U.K. : Emerald Publishing Limited, 2019)
This book provides new and innovative insights into the field of management and organization inquiry through theory, method, and research. It provides extensive coverage of the 7S structurethat has been so transformational for the field: Storytelling, System, Sustainability, Science, Spirit, Spirals, and Sociomateriality, showing how they evolved, how they interact, and possible futures for this discipline. These themes emerged during the 25 years of theStanding Conference for Management andOrganizational Inquiry (Sc'Moi). We realized that we haveto make space and time to get offthe path of 'business-as-usual' ways of working.We know how to make organizations more efficient, but we cannot steer them away from a short-term, quarterly return mindset. It takes a long temporal horizon to understand how we are depleting the resources that future generations will need to survive.The Emerald Handbook of Management and Organization Inquiryshines a light on a brighter way of working for the future: one that accommodates living and working within the limits of the world's resources.
Prelims -- Introduction -- The history of the standing conference for management and organization inquiry, its transitions and transformations -- Explorers of the future of management and organizational inquiry -- Index.
Includes index.
Print version record.
Keywords: Management; Organization; Business & Economics -- Management; Business strategy